Utility of Amrut Pushti Vardhak powder in enhancing physical fitness - Katti, Anand; ., Ashok; G., Phanikumar; K. R., Anilakumar (International Journal of Advances in Medicine, 2022)
Background: Physical performance depends on physical fitness. Fit persons can accomplish the tasks. Fitness is modifiable and hence the fitness level can be increased. In this background a need was felt to validate the efficacy of the Amrut Pushti Vardhak (APV) powder, a product developed by DFRL Mysore, for its physical performance enhancing activity by fitness tests. The result of pre-clinical study of the product was encouraging; hence clinical trial was taken up. Methods: All norms of good clinical practice and ethics were abided. The subjects were assigned in two homogenous groups, as control and trial groups. The trial group was given APV powder 30 gms/day for 21 days in the morning. The other group served as negative control. To evaluate the efficacy modified Harward step test was conducted before and after the intervention. Results: The test group showed statistically significant increase in the duration of exercise with p value 0.027 and increase in physical fitness index (PFI) with p value 0.01. The test group also showed statistically significant increase in the maximal oxygen consumption (VO2 max) (p=0.004). The increase in physical fitness level can be attributed to ingredients of APV powder. Conclusions: Healthy volunteers who received APV powder 30 gms/day for the duration of 21 days reported statistically significant increase in their duration of exercise, PFI and VO2 max. This indicates the APV powder increases in the physical fitness level.